2010
DOI: 10.1155/2010/829702
|View full text |Cite
|
Sign up to set email alerts
|

Home Range and Habitat Use of the New Zealand Falcon (Falco novaeseelandiae) within a Plantation Forest: A Satellite Tracking Study

Abstract: We tracked two adult and three juvenile New Zealand falcons (Falco novaeseelandiae) in Kaingaroa Forest pine plantation from 2002 to 2008 using Argos satellite technology. The home ranges for both adults and juveniles varied, ranging between 44 and 587 km 2 . The falcons occasionally utilised areas outside the forest and used stands of all ages within the forest, generally in proportion to their availability. For the most part, the juveniles remained within ca. 8 km of their nests and dispersed at 58, 69, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
(19 reference statements)
2
4
0
Order By: Relevance
“…DISCUSSION We found that the home-range size of New Zealand Falcons during the breeding season in a pine plantation varies among individuals, from 5.7 km 2 to 17.8 km 2 in males, and from 1.5 km 2 to 10.6 km 2 in females. This variation is within the range of home-range estimates recorded during other studies in the same habitat for males, but not for females (Thomas et al 2010). Thomas et al (2010) recorded the annual home range of one adult female to vary between 33 km 2 and 78 km 2 , suggesting that in some cases the home ranges of adult females can be considerably larger than recorded in this study.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…DISCUSSION We found that the home-range size of New Zealand Falcons during the breeding season in a pine plantation varies among individuals, from 5.7 km 2 to 17.8 km 2 in males, and from 1.5 km 2 to 10.6 km 2 in females. This variation is within the range of home-range estimates recorded during other studies in the same habitat for males, but not for females (Thomas et al 2010). Thomas et al (2010) recorded the annual home range of one adult female to vary between 33 km 2 and 78 km 2 , suggesting that in some cases the home ranges of adult females can be considerably larger than recorded in this study.…”
Section: Resultssupporting
confidence: 83%
“…This variation is within the range of home-range estimates recorded during other studies in the same habitat for males, but not for females (Thomas et al 2010). Thomas et al (2010) recorded the annual home range of one adult female to vary between 33 km 2 and 78 km 2 , suggesting that in some cases the home ranges of adult females can be considerably larger than recorded in this study. Variation in the tracking technique, timing of the study, and the home-range estimation method may explain some of the discrepancy between the two studies.…”
Section: Resultssupporting
confidence: 83%
“…On the basis of these criteria, the present paper develops a technologychoice decision guide to assist wildlife scientists in selecting an optimal tracking technology. We undertook four satellite-tracking case studies involving avian, aquatic and terrestrial species living in diverse environments of the world, including the following: three African elephants (Loxodonta africana), Kruger National Park, South Africa (Thomas et al 2008;Thomas et al 2011); five New Zealand bush falcons (Falco novaeseelandiae), central North Island, New Zealand (Thomas et al 2010c); one estuarine crocodile (Crocodylus porosus), Darwin, Australia (Thomas et al 2010a) and; three northern royal albatrosses (Diomedea sanfordi), Taiaroa Head, New Zealand (Thomas et al 2010b). We use these case studies to validate and test the technology-choice decision guide and to calculate the cost effectiveness of alternative tracking methods.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, Seaton (2007) noted that the home range size of breeding female falcons in Kaingaroa increased as their young became more self-sufficient. Thomas et al (2010a) analysed PTT/Argos satellite tracking data for two adult falcons (a male for one non-breeding season and a female for two non-breeding seasons) in Kaingaroa. and home range size of our study falcons appeared to be influenced principally by the distribution of the young/mature forest edge within their home ranges rather than by prey abundance alone.…”
Section: Discussionmentioning
confidence: 99%